MENINGKATKAN KUALITAS SUMBER DAYA MANUSIA DALAM PENDIDIKAN DENGAN PROGRAM KUNJUNGAN SMA ISLAM NABILAH, BATAM, INDONESIA KE UNIVERSITI TEKNOLOGI MALAYSIA, JOHOR BAHRU, MALAYSIA - Sarmini, Sarmini; Titik W, Diana; Ngaliman, Ngaliman; Mustika, Ita; Yanti, Sri (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2025)
In the world of education, it is very important to improve the quality of human resources. Because with good quality human resources in the world of education, it is a government program to achieve Golden Indonesia in 2045. The vision of high school students about higher education is good and open to choosing education in higher education. On this basis, SMA Islam Nabilah held a visit to Universiti Teknologi Malaysia (UTM) in Johor Bahru, Malaysia. Which was attended by 23 students and 5 accompanying teachers. The purpose of this visit is to improve the quality of human resources in education, by broadening horizons and understanding the choice of majors according to students' talents and interests. The visit was conducted on April 15-16, 2025. And received by a team from UTM consisting of 5 people.